Associations between Resident Perceptions of the Local Residential Environment and Metabolic Syndrome. (25th September 2012) - Baldock, Katherine; Paquet, Catherine; Howard, Natasha; Coffee, Neil; Hugo, Graeme; Taylor, Anne; Adams, Robert; Daniel, Mark
Abstract : A substantial body of research has arisen concerning the relationships between objective residential area features, particularly area-level socioeconomic status and cardiometabolic outcomes. Little research has explored residents' perceptions of such features and how these might relate to cardiometabolic outcomes. Perceptions of environments are influenced by individual and societal factors, and may not correspond to objective reality. Understanding relations between environmental perceptions and health is important for the development of environment interventions. This study evaluated associations between perceptions of local built and social environmental attributes and metabolic syndrome, and tested whether walking behaviour mediated these associations. Individual-level data were drawn from a population-based biomedical cohort study of adults in Adelaide, South Australia (North West Adelaide Health Study). Participants' local-area perceptions were analysed in cross-sectional associations with metabolic syndrome using multilevel regression models (n = 1, 324 ). A nonparametric bootstrapping procedure evaluated whether walking mediated these associations. Metabolic syndrome was negatively associated with greater local land-use mix, positive aesthetics, and greater infrastructure for walking, and was positively associated with greater perceived crime and barriers to walking . Walking partially mediated associations between metabolic syndrome and perceived environmental features. Initiatives targeting residents' perceptions of local areas may enhance the utility of environmental interventions to improve population health.